Community based natural resource management systems : an evaluation of the campfire programme in Zimbabwe : with special reference to Omay, and Makande Communal Lands in Nyaminyami District - Sibanda, Backson M C, 1950- (Rhodes University, Faculty of Science, Department of Geography, 1999)
Communal Areas Management for Indigenous Resources (CAMPFIRE) is an innovative community based natural resource management strategy which transfers management and conservation responsibility from the state to the local communities. This thesis critically examines CAMPFIRE's potential for introducing sustainable natural resource management through the detailed examination of CAMPFIRE's implementation in Nyaminyami District, which is located in the Zambezi Valley of Zimbabwe. Comparisons with other districts are made as appropriate. The theoretical framework of this research is based on an examination of common property theories, theories of bundles of rights, globalisation and the notion of global commons. It is also based on critically examining Zimbabwean, African and international literature dealing with the management of natural resources used in common. There are five specific contributions which the thesis makes. Firstly, common property management is redefined and the difference between resources used in common but which are not common property and common property resources is clarified. Secondly, the study shows that CAMPFIRE is not sustainable whilst it remains dependent on wildlife alone and on a single species - the elephant. Thirdly, the thesis has attempted to extricate the CAMPFIRE concept from the wildlife debate in which it has become entangled and, fourthly, it examines the issues of globalisation and the global commons to show how decisions made at the international level impact on resource utilisation and management at the local level. Finally, the study examines what residual Tonga indigenous knowledge still exists and which aspects can be incorporated into present management systems. Overall, the results of the research suggest that while CAMPFIRE is an innovative strategy for sustainable natural resource management it, has not achieved its major objective of becoming a grassroots rural development strategy. It has become a top down elitist programme which is NGO and donor driven and government constrained. Legislation and policy need formally to address this problem. Finally, the thesis recognises the potential of the CAMPFIRE concept, especially if the weaknesses ofthe programme are addressed.
Keywords: Natural resources -- Zimbabwe -- Management